2012
DOI: 10.1142/s1088424612500368
|View full text |Cite
|
Sign up to set email alerts
|

Separation and atropisomer isolation ofortho-halogenated tetraarylporphyrins by HPLC: Full characterization using 1D and 2D NMR

Abstract: The separation and isolation of the four atropisomers of orthohalogenated tetraaryl porphyrins by semipreparative HPLC is described. Full characterization and assignment of all 1 H and 13 C resonances of 5,10,15,20tetrakis(2fluoro or 2chlorophenyl)porphyrins and 5,10,15,20tetrakis(2 fluoro or chloro5Nethylsulfamoylphenyl)porphyrins by 1D and 2D NMR techniques is reported. The outcome is an unequivocal evidence of the chlorosulfonation of mesotetra(2haloaryl)porphyrins on the 5′position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…[42][43][44][45][46][47][48][49][50][51] The free porphyrin is isolated as a mixture of four atropisomers, as seen by the presence of four observable N-H resonances by 1 52 Attempts to separate the four isomers by TLC and HPLC were unsuccessful. 24 The ratio of the isomers in the free porphyrin cannot be clearly determined by NMR integration due to peak overlap, but the data do suggest that one isomer is present in higher abundance as compared to the other three. Similar behavior has been observed with the meso-tetrakis(2hydroxyphenyl)porphine (H 2 To-OHPP) first prepared by Gottwald and Ullman.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…[42][43][44][45][46][47][48][49][50][51] The free porphyrin is isolated as a mixture of four atropisomers, as seen by the presence of four observable N-H resonances by 1 52 Attempts to separate the four isomers by TLC and HPLC were unsuccessful. 24 The ratio of the isomers in the free porphyrin cannot be clearly determined by NMR integration due to peak overlap, but the data do suggest that one isomer is present in higher abundance as compared to the other three. Similar behavior has been observed with the meso-tetrakis(2hydroxyphenyl)porphine (H 2 To-OHPP) first prepared by Gottwald and Ullman.…”
Section: Resultsmentioning
confidence: 92%
“…21 Due to this wide versatility, both theoretical and experimental studies have addressed the underlying factors that influence the rotation of these aryl rings. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Unsymmetric substitution of the meso aryl ring can result in atropisomers, which arise from differing orientations of the aryl substituents above or below the porphyrin plane. Models have indicated that deformation of the porphyrin core from a planar configuration is required in order for these interacting substituents to pass one another in the transition state.…”
mentioning
confidence: 99%
“…Additionally, tetra-arylporphyrins with substituents in the ortho-positionsuch as ligands 2, 3 and 6 can have several atropisomers. 36,37 Also, in the case of ligand 1, a polydisperse mixture is present that can affect the HPLC signal. Hence, this may explain the broad peaks observed on the radio-HPLC traces with 52 Mn-(1) and 52 Mn-(6)as well as differences in retention time for the latter compound.…”
Section: Discussionmentioning
confidence: 99%
“…[27] The proton NMR spectrum was found to show multiple resonancesf or the methyl signal in 5,10,15,20-tetrakis(o-tolyl)porphyrin, which were attributedt o porphyrin atropisomerism and afull 1 Hand 13 Ccharacterization of individual porphyrin rotamers carriedo ut by Abraham et al [28] Atropisomeric effects have been described not only for the meso-substituentsb ut also for the porphyrin macrocycle, with distinct NMR signals observed for b-position protons. However, in the case of a,b,a,b and a 4 ,t he insignificants pectral differences, makes using only 1D or even most 2D [29] NMR techniques inadequate to identify all isomersd ue to the high symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Atropisomeric effects have been described not only for the meso‐substituents but also for the porphyrin macrocycle, with distinct NMR signals observed for β‐position protons. However, in the case of α,β,α , β and α 4 , the insignificant spectral differences, makes using only 1D or even most 2D [29] NMR techniques inadequate to identify all isomers due to the high symmetry.…”
Section: Introductionmentioning
confidence: 99%